Analysis of Students' Ability to Understand Mathematical Concepts in The Material Relations and Functions - Abdulhafiz; Alfi Yunita; Lita Lovia (Rangkiang Mathematics Journal, 2023)
The role of mathematics needs serious attention, considering its benefits in everyday life. Mathematics lessons are provided starting from elementary school to tertiary institutions in order to equip students to have the ability to think logically, critically, and creatively. The low ability to understand students' mathematical concepts is due to the fact that previously, students carried out online learning, so the teaching carried out was not adequate, and many students did not do the assignments given, resulting in students not understanding mathematical concepts correctly. The purpose of this study was to describe the ability to understand mathematical concepts of class VIII.1 students of SMP Negeri 2 Tanjung Raya. The subjects of this research were class VIII.1 students of SMP Negeri 2 Tanjung Raya. The research method used is a descriptive method with a qualitative approach. The sampling technique used purposive sampling. Instruments are used to collect data in the form of tests of ability to understand the concept, interviews, and documentation. The test results were analyzed based on indicators of understanding the concept. The results of the research on academic ability related to the ability to understand concepts are high, medium, and low from the test results.